PENERAPAN MODEL PEMBELAJARAN EXPLICIT INSTRUCTION UNTUK MENINGKATKAN HASIL BELAJAR SISWA POKOK BAHASAN CAHAYA DAN SIFATNYA PADA SISWA KELAS V DI SD NEGERI 1 SEMBAWA - Agus Saeful Anwar; Peti Lapenia (Universitas Muhammadiyah Kuningan, 2019)
The background of this research is that student learning outcomes are still low, this is evidenced from the data obtained which shows that the average value of science learning outcomes is 55 obtained under the specified completeness criteria (KKM) which is set at 70. This study aims to determine the application of explicit instruction learning model to improving student learning outcomes on the subject of light and its nature. The study design used pre-experimental design with the form of one group pretest-posttest design. The population in the study were grade V students, amounting to 21 students. Sampling using the total sampling technique. The results showed that the average pretest results in the sample class were 56.36. While the average posttest results after being treated by applying the explicit instruction learning model in the sample class is 88.43. Based on the normality test, the sample class data is normally distributed. Based on the homogeneity test, the sample class data obtained is homogeneous distribution. Hypothesis testing using t test. From the results of the t-test, the value of 10.98 or> t table (0.05; 40) is 1.68, so it can be concluded that Ho is rejected and H1 is accepted. Thus, there is the effect of applyinglearning model explicit instruction on improving student learning outcomes on the subject of light and its nature in class V SD Negeri 1 Sembawa.